Penyelesaian Pembiayaan Bermasalah di KSPPS Bina Syariah Ummah Cabang Bawean - Hanif Azhar; Sarifatul Aini; Intan Widuri (CENDEKIA: Jurnal Studi Keislaman, 2022)
Abstract: This research was conducted to answer several questions: What are the causes of problematic financing at KSPPS Bina Syariah Ummah Bawean Branch?, what steps have been taken to deal with this problem?, and what steps have been prepared to minimize the potential for problematic financing to arise in the future ?. This research uses a type of normative-empirical legal research with a conceptual approach, a statutory approach, and a case study approach to legal events. The data used are primary data and secondary data. Primary data sources were obtained from interviews with the KSPPS Bina Syari'ah Ummah Bawean Branch. Secondary data sources were obtained from literature studies and document studies. Data collection techniques were carried out by document studies and interviews. The results of this study concluded that the factors causing problematic financing at KSPPS Bina Syariah Ummah Bawean Branch consisted of 2 aspects: internal and external. Internal aspects (cooperatives) in the form of not implementing the precautionary principle properly. While external factors (partners) are dishonesty and indiscipline, non-permanent income, business failures and disasters that befall their businesses. There are two settlement procedures used: rescheduling and collateral execution (selling collateral). While preventive measures are carried out by actually implementing the Management Operational Standards in a preventive (prevention) and curative (resolving efforts) way.Keywords: problem financing, KSPPS, Bina Syariah Ummah, Bawean Branch Abstrak: Penelitian ini dilakukan guna menjawab beberapa pertanyaan: Apa penyebab pembiayaan bermasalah di KSPPS Bina Syariah Ummah Cabang Bawean ?, langkah apa saja yang telah dilakukan guna menangani masalah ini ?, dan langkah apa saja yang dipersiapkan untuk meminimalisir potensi timbulnya pembiayaan bermasalah di masa mendatang ?. Penelitian ini menggunakan jenis penelitian hukum normatif-empiris dengan pendekatan konseptual, pendekatan perundang-undangan, dan pendekatan studi kasus pada peristiwa hukum. Data yang digunakan berupa data primer dan data sekunder. Sumber data primer didapat dari wawancara kepada pihak KSPPS Bina Syari’ah Ummah Cabang Bawean. Sumber data sekunder diperoleh dari studi kepustakaan dan studi dokumen. Teknik pengumpulan data dilakukan dengan studi dokumen dan wawancara. Hasil penelitian ini menyimpulkan bahwa faktor penyebab terjadinya pembiayaan bermasalah di KSPPS Bina Syariah Ummah Cabang Bawean terdiri dari 2 aspek: internal dan eksternal. Aspek internal (koperasi) berupa tidak dijalankannya prinsip kehati-hatian dengan benar. Sementara faktor eksternal (mitra) berupa ketidakjujuran dan ketidakdisiplinan, penghasilan bukan dari pekerjaan tetap, kegagalan usaha dan musibah yang menimpa usahanya. Prosedur penyelesaian yang digunakan ada dua: rescheduling (penjadwalan kembali) dan eksekusi jaminan (menjual jaminan). Sementara langkah pencegahan dilakukan dengan benar-benar melaksanakan Standar Operasional Manajemen dengan cara preventif (pencegahan) dan kuratif (upaya penyelesaian).Kata kunci: pembiayaan bermasalah, KSPPS, Bina Syariah Ummah, Cabang Bawean